The smart money woman: An African girl's journey to financial freedom - Ugwu, Arese (Lagos, Nigeria Matador, Kibworth Beauchamp, 2016)
"Meet Zuri. Shes living a fabulous life. Great car, gorgeous apartment, well paid job. Meet Zuri. Broken down car, an apartment she can't afford, a job she's about to lose. What's a broke girl to do? With her best friends Tami (the flighty fashion designer), Lara (the tough oil and gas executive), Adesuwa (the conservative lawyer), and Ladun (the fabulous housewife), Zuri grows a little, learns a lot and navigates her way to making better financial decisions and building wealth. This book tackles, debt, spending, the consumerist culture of the African middle class, the fear and misconceptions surrounding money and the lack of it, love, friendships, cultural and societal pressures and the roles they play in success. With each chapter comes a Smart Money Lesson, there to help you work your way up the financial ladder"
Matador® is an imprint of Troubador Publishing Ltd
Loans
nmn, 23/12/2022